Kwestie prawno-ustrojowe w pracach nad konstytucją kwietniową z 1935 roku - Bojko, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The April Constitution ended the process of evolution of the political system of prewar Poland. She broke with the principles of liberal democracy and sanctioned the position of the office of the president of Poland as the authoritarian sovereign legally. The sanation Constitution was a Polish reply to the intellectual climate of the thirties. Drawing mainly upon archive materials, the author acquaints the reader with the legal and political subject matter of the April Constitution and with legal argumentation for the reconstruction of the political system of the Second Republic of Poland.
Keywords: sanacja; konstytucja kwietniowa 1935; autorytaryzm